2011
DOI: 10.1007/s00198-011-1736-5
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic status, race, and bone turnover in the Midlife in the US Study

Abstract: Purpose To determine socioeconomic status (SES) and race differences in levels of bone turnover. Methods Using data from the Biomarker Substudy of the Midlife in the U.S. (MIDUS) study (491 men, 449 women), we examined cross-sectional associations of SES and race with serum levels of bone turnover markers (bone-specific alkaline phosphatase [BSAP], procollagen type I N-terminal propeptide [PINP], and N-telopeptide [Ntx]) separately in men and women. Linear multivariable regression was used to control for bod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 79 publications
0
12
0
Order By: Relevance
“…However, even results from community‐based studies are conflicting. For instance, in the Midlife in the US Study (MIDUS), low family poverty‐to‐income ratio was associated with higher levels of bone turnover markers (adjusted for age, race, body weight, and clinical site) among men . Combined results from 729 MIDUS men and women showed that lumbar spine BMD was higher with higher childhood SES ( p = 0.009) and in college graduates versus those without college education ( p = 0.01) (independent of race and other covariates).…”
Section: Discussionmentioning
confidence: 99%
“…However, even results from community‐based studies are conflicting. For instance, in the Midlife in the US Study (MIDUS), low family poverty‐to‐income ratio was associated with higher levels of bone turnover markers (adjusted for age, race, body weight, and clinical site) among men . Combined results from 729 MIDUS men and women showed that lumbar spine BMD was higher with higher childhood SES ( p = 0.009) and in college graduates versus those without college education ( p = 0.01) (independent of race and other covariates).…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-eight patients were receiving an SSRI prior to entering the study and discontinued this drug 2 weeks prior to beginning the open-label study treatment. Analyses were conducted in European-Americans only for various reasons: First, differences in bone metabolism were described varying among different populations (e.g., Crandall et al 2012). Second, the allele frequencies typically vary among ethnic groups (Gelernter et al 1997) and population stratification may result in spurious findings.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies are now targeting SEP as a risk factor for poor bone health, raising public health concerns. In these studies [3][4][5][6][7][8], low SEP is associated with low bone mineral density (BMD) and/or increased risk of osteoporosis (or osteoporotic fractures), which may be explained by less protective behaviors in low-SEP individuals. Low SEP can negatively influence bone health and increase the risks of osteoporotic fractures, which deteriorate quality of life [9].…”
mentioning
confidence: 98%